Amplification of the tunnel current in the redox-mediated tunneling contacts. (20th December 2015) - Medvedev, Igor G.
Highlights: Amplification of tunnel current as a function of the bias voltage can have a maximum. Maximum value of amplification increases with the increase of the Debye screening. It also increases with the increase of the reorganization free energy. Simple approximate expressions for amplification are obtained. Abstract: Dependence of amplification A of the tunnel current in the electrochemical bridged tunneling contact on the bias voltage V, reorganization free energy E r, intensity of Debye screening in the tunneling gap and the asymmetry parameter d is studied. The non-adiabatic electron tunneling through a one–level redox molecule is considered within the wide-band approximation for the electronic structure of the working electrodes. It is shown that, in the limit of the full Debye screening, amplification increases monotonously with the increase of V and approaches rather large limiting value A lim which, in its turn, increases with the increase of E r and d . In the realistic case of the intermediate Debye screening amplification increases at first with the increase of V, then reaches a maximum A max at some value V max and, when V farther increase, decreases to A = 1. The functions A ( V ) are calculated for different values of the parameter of the tunneling contact and it is shown that A max increases with the increase of E r, d and the intensity of Debye screening. The approximate analytical expressions for A max and V max which show in the explicit form their dependence on the parameters of the system are presented.